Lexical Characteristics of Computer Terms in English, Uzbek and Karakalpak Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The examination of computer and Internet terms and their comparative comparison between the Uzbek Karakalpak and English languages is one of the real issues; this is thought to be the foundational study in Uzbek linguistics.